Assessment of Neonatal Intensive Care Unit Sound Exposure Using a Smartphone Application - Capriolo, Christine; Viscardi, Rose M.; Broderick, Karen A.; Nassebeh, Sepideh; Kochan, Michael; Solanki, Nina S.; Leung, Jocelyn C. (American Journal of Perinatology, 2020)
Objective This study aimed to determine the impact of neonatal intensive care unit (NICU) design and environmental factors on neonatal sound exposures. We hypothesized that monitoring with a smartphone application would identify modifiable environmental factors in different NICU design formats.Study Design Minimum, maximum, and peak decibel (dB) recordings were obtained using the Decibel X phone app, and the presence of noise sources was recorded in each patient space at three NICUs over a 6-month period (December 2017 to May 2018). Data were analyzed by Student's t-test and ANOVA with Bonferroni correction. Data were collected at the University of Maryland Medical Center single family room (SFR) level IV and St. Agnes Healthcare hybrid pod/single family room level III NICU, Baltimore, MD and at Prince George's Hospital Center open-pod design Level III NICU, Cheverly, MD.Results All recordings in the three NICUs exceeded the American Academy of Pediatrics (AAP) recommended <45 dB level. The maximum and peak dB were highest in the open pod format level III NICU. Conversations/music alone and combined with other factors contributed to increased sound exposure. Sound exposure varied by day/night shift, with higher day exposures at the level III hybrid and open pod NICUs and higher night exposures at the level IV SFR NICU.Conclusion Although sound exposure varied by NICU design, all recordings exceeded the AAP recommendation due, in part, to potentially modifiable environmental factors. A smartphone application may be useful for auditing NICU sound exposure in quality improvements efforts to minimize environmental sound exposure.Key Points
Keywords: NICU design; sound exposure; smartphone application; sound monitoring